Relationship between the use of new technologies and musculoskeletal symptoms in children and adolescents - Santos, Paula Clara (2018)
Childhood and adolescence are determinants of musculoskeletal development, and the attitudes and habits adopted during these periods can have repercussions in adult life. The increasing use of technologies is becoming more worrying due to the sustained and prolonged postures due to the use of these devices and the consequent impact on musculoskeletal health.